Climate Change and the Struggle for Climate Justice - Ikporukpo, Chris O.; Ikporukpo, Ninane Nina (Advances in Social Sciences Research Journal, 2024)
Climate change is one of the greatest global challenges. The phenomenon and actions taken to address it have thrown up some contentious issues. One of such issues is climate justice. This paper analyses the bases for climate justice and the attempts at achieving it. The basic sources of data were the publications/documents of the United Nations Framework Convention on Climate Change (UNFCCC) secretariat and the Intergovernmental Panel on Climate Change (IPCC). Information was also obtained from the publications and websites of the climate negotiation blocs, such as G77 + China and Alliance of Small Island States (AOSIS), and several Civil Society Organisations (CSOs) such as Climate Action Network, Oxfam, GreenPeace and Third World Network. The climate justice struggle has been necessitated mainly by two driving forces. These are the experiences of the impact of climate change and the environmental legal principles that have emerged from environmental and climate change challenges. In spite of the fact that climate change and its impact are global, vulnerabilities vary across regions and socio-economic groups. The disproportionate impact of climate change is one of the drivers of the struggle for climate justice. The environmental/climatic legal principles that have formed bases for the climate justice struggle derive largely from UNFCCC, the Rio Declaration and the Paris Agreement. They are, to an extent, related to the Principle of Disproportionate Climate Burden. The principles include Common But Differentiated Responsibilities, Polluter Pays, No-Harm (to others) and Beneficiary Pays. Strategies employed in the struggle for climate justice include advocacy, focused negotiations at CoPs, protests/strikes, and litigation. Although, the developing countries have been the leaders in the struggle for climate justice, CSOs have been particularly prominent. The demand for increased financing of climate mitigation and adaptation has been characteristic. The struggle has resulted in more climate action. However, the ultimate focus must be the achievement of net zero emissions.